The Effect of Interest in Changing the Legal Provisions - Al-Issa, Harith (Dirasat: Shari'a and Law Sciences, 2021)
The study aims to show that the interests of the worshipers influenced the change of rulings as the Islamic Sharia came to take into account their legitimate interests. This study deals with the impact of interest in the change of sharia rulings. The researcher adopted the inductive method to extrapolate the statements of the fundamentalists from their various books. It also adopted the descriptive method to track the hadiths that provoke the change of judgments depending on the change of interests and the analytical method in the analysis, interpretation and guidance of Quranic verses and hadiths on this issue. The study concluded that the whole Sharia is based on interests, either to bring benefit or to ward off spoilers. As for the fixed ones, there is no way to change them until the Day of Judgment, and this change can only be made by a diligent person who is all-inclusive of the conditions of Ijtihad. The study recommends the importance of paying attention to Sharia colleges, Ifta, and fiqh councils and to take into account the issues whose rulings change with changing interests, publish them to the public and encourage graduate students to devote research papers on them.